Destructive (Erosive) Tufted Angioma/Kaposiform Hemangioendothelioma of the Eyelid - Abdel-Naser , M. Badawy; Altenburg, Andreas; Wollina, Uwe; Zouboulis, Christos (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Tufted angioma/kaposiform hemangioendothelioma represents a spectrum of rare benign skin vascular neoplasms that differ in the extent and prognosis. Tufted angioma affects primarily children, is localized to skin, shows no tendency for ulceration or tissue invasion and has a favorable prognosis. CASE REPORT: In this case report, tufted angioma involved the lower eyelid resulting in its destruction and compromised its function, hence necessitating rapid surgical excision to preserve the function of eyelid. CONCLUSION: TA/KHE is a rare vascular benign neoplasm usually asymptomatic but may affect delicate structures, such as the eyelid resulting in destruction and hence may require rapid surgical intervention. corresponding eye.